Analysis Of Revenue Utilization Fisherman Families In The Village Plow The City Of Bengkulu - Aften Hagriansyah; Duharman, Duharman; Milla , Hilyati (Universitas Dehasen Bengkulu, 2025)
This study aims to determine: How much is the average income of fishermen's households, How much is the expenditure of fishermen's households, How much is the utilization of fishermen's household income in Bajak Village, Bengkulu City. This research was conducted in Bajak Village, Bengkulu City, this study used a qualitative approach with the type of field research in Bajak Village. This research was conducted in April-May 2025. The number of samples used was 10 respondents. Data analysis was carried out qualitatively. The results of the study showed that the average income of fishermen in Bajak Village during the fishing season is around IDR 500,000-IDR 1,000,000 per sail, if it is a lean season they only get around IDR 200,000, some even get nothing at all. Household expenditure of fishermen to meet their daily needs average Rp. 50,000-Rp. 100,000, the most important of which are basic needs such as rice, children's school, kitchen necessities, and so on which have indeed become their main needs. The utilization of fishermen's income fulfills their primary needs, which generally include nutritious food, decent housing, clothing, and access to clean water, while their secondary needs generally include ship equipment, education and health. The availability of capital to buy better fishing gear, as well as the need for maintenance and repair of boats and fishing gear, are the main priorities.